Detection of coastline erosion by remote sensing approach a case study: along the coast of Tanjung Piai / Nur Efa Damayanti Mansuri - Mansuri, Nur Efa Damayanti (2020)
Coastal erosion is becoming a growing problem all over the world. Coasts are very diverse environments that are continually evolving. The transition is attributed to three major mechanisms, such as flooding, transport and precipitation, which work on the coast. Coastal erosion relies on multiple environmental causes such as hurricanes, seas, weather, tides, near-shore rivers, slope cycles, vertical ground motions. Erosion attributable to human activities can involve clearance of beach material, building activity, shifting direction of flow of sediment, etc. Marine management techniques are used to shield marine property from erosion. Coastal defenses are primarily used in coastal protection schemes with the purpose of avoiding coastal degradation and floods in the hinterland. Such goals include the defense of harbor basins and port openings from tides, the strengthening of shipping channels and inlets, and the security of water intakes and outlets. There are three major classes of concrete systems that shield the soil or the beaches. The study of monitoring and analysis of coastline change and erosion prediction has been widely used satellite imagery. Satellite data that is often used in monitoring studies and analysis of coastline changes are Landsat, Quickbird, Alios, SPOT, IKONOS, etc. The aim of study is to study the influence of coastal dynamic action on the erosion of coastline happened in Tanjung Piai, Johor, Malaysia by using SPOT 7 in 2015 and 2019, has a spatial resolution 1.5 m. As a result, identification of the changes can made by land cover area. The covered by land for 2015 was 345677.78 ha (67 per cent) and 36872.78 ha (33 per cent) for 2019. The difference for both years is 16872.00 ha (2 percent). This indicates that the coastline of Tanjung Piai, Johor, faces changing coastlines from 2015 to 2019.